A conceptual framework to evaluate the impact of innovation platforms on agrifood value chains development - Cadilhon, Joseph J. (2013)
Innovation platforms are equitable, dynamic spaces designed to bring heterogeneous actors together to exchange knowledge and take action to solve a common problem. Although innovation platforms are being set up to attain collectively defined development objectives, there are limited methods and tools available using quantitative data to evaluate whether they are effective. This paper elaborates a conceptual framework based on elements from new institutional economics and marketing relationship management to model the impact pathways within innovation platforms and how they contribute to attaining the objectives of the rural communities involved. The paper also proposes a field research protocol based on focus group discussions, semi-directive interviews of key stakeholders associated with the innovation platforms and individual surveys of platform members. The data collected is both qualitative and quantitative in nature allowing useful triangulation to test the model. Successive empirical tests of the model in different contexts should allow long-term strengthening and field validation of the conceptual framework.